Simultaneous Modulation of Magnetic and Dielectric Transition via Spin‐Crossover‐Tuned Spin Arrangement and Charge Distribution - Zheng, Hui; Meng, Yin‐Shan; Zhou, Guang‐Li; Duan, Chun‐Ying; Sato, Osamu; Hayami, Shinya; Luo, Yi; Liu, Tao (Angewandte Chemie International Edition, 2018)
Magnetic and dielectric properties have been tuned simultaneously by external stimuli with rapid and sensitive response, which is crucial to monitor the magnetic state via capacitive measurement. Herein, positive charged FeII ions were linked via negative charged [(Tp)FeIII(CN)3]− (Tp=hydrotris(pyrazolyl)borate) units to form a neutral chain. The spin‐crossover (SCO) on FeII sites could be sensitively triggered via thermal treatment, light irradiation, and pressure. SCO switched the spin state of the FeII ions and antiferromagnetic interactions between FeIII and FeII ions, resulting in significant change in magnetization. Moreover, SCO induced rotation of negative charged [(Tp)FeIII(CN)3]− units, generating dielectric anomaly due to geometric change of charges distribution. This work provides a rational way to manipulate simultaneous variations in magnetic and dielectric properties utilizing SCO as an actuator to tune spin arrangement, magnetic coupling, and charge distribution. Magnetic interactions: A spin‐crossover‐actuated magnetic and dielectric transition has been observed. The sensitive response to hydrostatic pressure and large dielectric anomaly could be attributed to a cooperative effect and rotation of the negative charged building block.